MODEL PROBLEM BASED LEARNING KOMPETENSI KOMUNIKASI INTERPERSONAL PADA MAHASISWA KEBIDANAN - Noor Azizah; Ana Zumrotun Nisak; Ika Tristanti (Universitas Muhammadiyah Kudus, 2022)
One method that is widely used to increase student activity in the learning process is the problem based learning method. Problem based learning builds skills, teamwork and communication. PBL is easier to implement and requires less preparation time when compared to classical learning methodsObjective: to apply problem-based learning model to interpersonal communication competenceMethod: observational method with problem based learning. The sample in this study were 15 students of the third semester of midwifery study program. Stages of analyzing, solving problems of cases, planning information communication and education, planning the media used in IEC, simulation of interpersonal communication and evaluation. The measuring instrument used is the Interpersonal Communication Competence Scale (ICCS).Result: the use of problem based learning interpersonal communication model for midwifery students found that most of the communication skills were 86.67% in good category and 13.33% in sufficient category.Conclusion: the problem based learning method with interpersonal communication competence is very effective in improving student learning outcomes, namely being more confident in conveying the message given to the audience.